An a priori shift in non-reductionist accounts of testimony - Malagutti, Gabriel Lucas Marques (2023)
Non-reductionism is the main framework in the epistemology of testimony. It states that absence of negative evidence is sufficient to justify testimonial acceptance. Lackey (2006; 2008) has put forward the strongest objection to non-reductionism. A case where in the total absence of negative evidence, one is still unjustified in accepting the speaker’s testimony. The goal of this research is to assess if, and how, non-reductionism can reply to the case. I will argue that most non-reductionist accounts appeal to background information to enable prima facie entitlement. I will argue that this is a structural flaw of a posteriori non-reductionist accounts, falling under Faulkner (1998)’s description of reductionism. Given the appeal to background information, such accounts are unable to successfully reply to the alien case. I will argue that the only account that is able to avoid both the charges of reductionism and to successfully reply to Lackey’s case, is Tyler Burge (1993)’s a priori account. I will argue, additionally, that a priori non-reductionism, exemplified by Burge, is the only kind of non-reductionism available to proponents of non-reductionism. An a priori shift in non-reductionist accounts of testimony must take place.